2015
DOI: 10.18632/oncotarget.6129
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mitochondrial RNA polymerase in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) cells have high oxidative phosphorylation and mitochondrial mass and low respiratory chain spare reserve capacity. We reasoned that targeting the mitochondrial RNA polymerase (POLRMT), which indirectly controls oxidative phosphorylation, represents a therapeutic strategy for AML. POLRMT-knockdown OCI-AML2 cells exhibited decreased mitochondrial gene expression, decreased levels of assembled complex I, decreased levels of mitochondrially-encoded Cox-II and decreased oxidative phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…Specifically, there are several ribonucleosides analogues, originally developed for antiviral therapy, which are substrates and inhibitors of human mitochondrial RNA polymerase (POLRMT) [ 33 ], and can be repurposed for cancer therapy. In preclinical studies the 2-C-methyladenosine ribonucleoside (2’-C-MeA) was shown to reduce mitochondrial gene expression and increase cell death in acute myelogenous leukemia (AML), while treatment of normal human hematopoietic cells did not alter clonogenic growth [ 27 ]. Due to the ancestral relationship between bacteria and mitochondria, several classes of antibiotics, including tetracyclines (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, there are several ribonucleosides analogues, originally developed for antiviral therapy, which are substrates and inhibitors of human mitochondrial RNA polymerase (POLRMT) [ 33 ], and can be repurposed for cancer therapy. In preclinical studies the 2-C-methyladenosine ribonucleoside (2’-C-MeA) was shown to reduce mitochondrial gene expression and increase cell death in acute myelogenous leukemia (AML), while treatment of normal human hematopoietic cells did not alter clonogenic growth [ 27 ]. Due to the ancestral relationship between bacteria and mitochondria, several classes of antibiotics, including tetracyclines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of mitochondrial ribogenesis is also a promising anti-cancer approach [ 25 , 26 ]. Mitoribogenesis can be hindered by drugs targeting POLRMT-mediated mt-rRNA transcription, like 2'C-Methyl-Adenosine (2’-C-MeA), as recently reported in acute myelogenous leukemia studies [ 27 ]. Moreover, due to the conservation between bacteria and mitochondria, antibiotics inhibiting bacterial protein synthesis (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggest that inhibition of mitochondrial gene expression may be of therapeutic value in the treatment of certain forms of cancer (e.g., acute myeloid leukemia). [16][17] Based on the obtained results and chemical evaluation, our validated inhibitors therefore provide promising starting points for a follow-up medicinal chemistry optimization program to generate druglike leads that are suitable for further development.…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, a 2-C-methyladenosine (2-CM), which functions as a chain terminator of mitochondrial transcription, was shown to decrease acute myeloid leukemia cell growth in a mouse xenograft model. 17 The inhibitors identified here may be useful in further studies for effects on those specific forms of drug-resistant cancers, including lymphomas and Varying concentrations of analogs were added, as indicated in the figure. All reactions contained uridine triphosphate (UTP) (200 µM) and α-32 P guanosine triphosphate (GTP) (see Materials and Methods for details).…”
Section: Discussionmentioning
confidence: 99%
“…Discovery of this compound was particularly notable, as mitochondrial proteases represent a class of enzymes for which few specific inhibitors had previously been available (Cole et al, 2015). Another study characterized the activity of 2-C-methyladenosine, a commonly used antiviral agent, as a specific inhibitor of POLRMT, the mitochondrial RNA polymerase (Bralha et al, 2015).…”
Section: Chemical Tools For Manipulating Mitochondrial Protein Synthementioning
confidence: 99%